The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1099/jmm.0.47151-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of aflatoxin B1 in liver biopsies of proven hepatocellular carcinoma in India determined by an in-house immunoperoxidase test

Abstract: Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer-related death in the world. The incidence of HCC in India is reportedly low and varies from 0.2 to 1.9 %. Aflatoxins, secondary metabolites produced by Aspergillus flavus and Aspergillus parasiticus, are potent human carcinogens implicated in HCC. The prevalence of aflatoxin B1 (AFB1) as co-carcinogen was analysed using an in-house immunoperoxidase test in 31 liver biopsies and 7 liver-resection specimens from histopathologically proven HCC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…Murugavel et al 67 from South India revealed that liver biopsies of HCC, the aflatoxin was detected in 58% of cases and no cirrhosis case was found to be positive for aflatoxin. It was therefore the patients had a possible history of AFB1-contaminated foodstuffs, which has acted either as a primary or additional risk factor for HCC.…”
Section: Role Of Aflatoxin B Causes Hepatocellular Carcinoma In Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…Murugavel et al 67 from South India revealed that liver biopsies of HCC, the aflatoxin was detected in 58% of cases and no cirrhosis case was found to be positive for aflatoxin. It was therefore the patients had a possible history of AFB1-contaminated foodstuffs, which has acted either as a primary or additional risk factor for HCC.…”
Section: Role Of Aflatoxin B Causes Hepatocellular Carcinoma In Indiamentioning
confidence: 99%
“…59 In India the prevalence of Figure 1 Hepatitis C and diabetes mellitus. 67 [(AFR, African; AMR, The Americas; EMR, Eastern Mediterranean; EUR, European; SEAR, South-East Asian; and WPR, Western Pacific), as defined in the GBD 2000 project. Each region is designated by the three-or four-letter region code followed by a one-letter suffix, corresponding to the mortality pattern of its member countries: A = very low child, low adult mortality; B = low child, low adult mortality; C = low child, high adult mortality; D = high child, high adult mortality; and E = high child, very high adult mortality].…”
Section: Impact Of Diabetes As Risk Factor In Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Periodic outbreaks of aflatoxicosis occur due to ingestion of contaminated food and result in hundreds of human deaths in Asia and Africa [5,6]. Furthermore, 58% of liver biopsies in cases of hepatocellular carcinoma have shown presence of aflatoxin B 1 (AfB 1 ) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Primary human liver cancer, of which hepatocellular carcinoma (HCC) is the predominant type, is a major cause of cancer death worldwide [1], accounts for about 90% of all cases of liver cancer and is the fourth most common cause of cancer mortality [2]. In 2009 liver cancer incidence in lower middle income countries accounts 10.2% of the total health care cost while in upper middle countries liver cancer resulting 1.9% and in high income countries the number of liver incidence which is accounting 2.7% of economic burden [3].…”
Section: Introductionmentioning
confidence: 99%